Iconografia monçoeira: imagens e ideologia - Hessel, Rodolfo Jacob (2006)
The dissertation has as main proposal, to analyze as the iconography monçoeira was adapted by a political elite and learned inhabitant from São Paulo, a project idealize begun with the objective of executing São Paulo as the largest responsible for the formation of the Brazilian nation, creating for that the idealize pioneer in the end of the century XIX and beginning of the XX. The Monções interfere in that project, because they appear as one of the ideological supports for it implementation, mainly, for being a fluvial road that it was derived of a road used by the pioneers in the century XVIII, until becoming a commercial route that linked Porto Feliz to the gold mines of Cuiabá in a long and difficult trip. The largest implementation of that whole construction iconographic was it then director of the Museum From São Paulo Afonso de Taunay, that was used of a great visual apparatus as pedagogic instrument before the population, his writing and his contusing rhetoric served as support in that process, it was during his administration that several pictures were ordered and formed a room dedicated to the Monções. The image, of this sorts things out, it comes as source of inclusion multidiscipline that dialogues, above all, with a produced textual narrative. This way, it intends to interpret and to analyze the use of the images of the Monções, for an elite from São Paulo, with the support of the public patronage for the construction of a speech nationalism and ideologic. The research emphasizes the importance of a historical moment and it relationship with the history from São Paulo and the national, identifying the point of prominence of that expansionist movement and its connection with an elitist process, that it aimed at to put São Paulo instead of prominence before the remaining of the country